Motives of social and environmental initiatives of large corporations located in Brazil - Silva, Jorge Vieira da; Amorim, Maria Cristina Sanches; Manso Júnior, Glauco Monteiro Cavalcanti (Pensamento & Realidade, 2017)
This article’s objective is to report an ongoing research, since 2007, related to the motives of social and environmental initiatives of large corporations located in Brazil. This research, based on managers and business owners’ interviews, investigating their motivation for social and environmental initiatives related to their business stakeholders, had demonstrated two main groups of motives: 1) “correct initiatives due to ‘wrong’ motives”, i.e. avoid sanctions (and losses) from local government authorities and avoid bad business image (or promote a good image) and, 2) “correct initiatives due to ‘correct’ motives”, i.e. ethical reasons, and long-term profit. Some executive’s answers had indicated that social and environmental initiatives were considered inherent of their business and, for the second group, these initiatives were also profitable, what implicates a requirement of a strategy simultaneously competitive and responsible.